Health related quality of life and related factors among bank call center employees [Banka çağri merkezi çalişanlarinda sağlikla ilişkili yaşam kalitesi ve ilişkili faktörler] - (:unkn) unknown (Nobelmedicus, 2016)
Objective: The purpose of this study was to investigate health related quality of life (HRQOL) and related factors among bank call center employees. Material and Method: The sample consisted of 201 employees. We evaluated HRQOL by using SF-36. The Pearson's correlation coefficients, independent groups t-test and one-way ANOVA test were used for data analyses. Results: Overall, 47.8% of the subjects stated that their workplace was mostly stressful. Almost all (95.5%) workers reported that their workplaces were noisy; 56.2% of them described themselves as “mildly noise annoyed”, and 43.8% as “severely annoyed”. Perceived job stress, noise annoyance and job dissatisfaction were associated with poor HRQOL. Musculoskeletal discomfort, headache, concentration difficulty, nervousness and fatigue were the most prevalent complaints. All health problems were associated with poor HRQOL. Conclusion: In conclusion, clarification of effecting factors on HRQOL of bank call center workers will drive the call center sector for the implementation of interventions towards preventing deleterious effects on health and HRQOL of their workers and towards creating a happy and healthy work environment. © 2016, Nobelmedicus. All rights reserved.
Keywords: Call center; Health complaints; Health-related quality of life; Job satisfaction; Perceived job stress; Perceived noise annoyance; Quality of life